(untitled) (Research Papers, 2023)
In present-day economic conditions characterized by growing complexity of business transactions, structural changes in the global economy and penetration and >penetration and the the broader use of information and communication technologies lead to a significant increase in operational risk. As this is a trend that will accelerate in the coming years, the paper argues that it is essential for banks to have adequate procedures in place to identify, analyze, evaluate, monitor and control this risk in order to determine economic capital, providing protection against the risks to which the financial institution is exposed.